Time discounting, present biases, and health-related behavior - Myong-Il Kang; Shinsuke Ikeda (Osaka University, Institute of Social and Economic Research (ISER), 2013)
Analysis of an original nationwide Internet survey reveals that health-related behavior shows associations with three aspects of time discounting: (i) impatience, measured by the overall discount rate; (ii) present bias, measured by the degree of declining impatience in the generalized hyperbolic discount function; and (iii) the sign effect, in that future losses are discounted at a lower rate than future gains. Present-biased respondents are classified as naïve if the responses are indicative of being a time-inconsistent procrastinator, and classified as sophisticated otherwise. The health-related indicators that we examine relate to smoking, health condition, dentition status, and body habitus. We first show that a higher degree of impatience tends to worsen health-related attributes. Second, respondents with more steeply declining impatience tend to develop more unhealthy behavior and ill-health conditions, and the tendencies are likely to be stronger for naïfs than for sophisticates. Third, the sign effect, too, shows an association with health-related behavior, although the significance levels are not overly high. Consistent with these findings, the principal component of the health-related measures shows strong associations with the degrees of impatience and declining impatience.
Keywords: I1; D03; D90; 330; health; time preference; discount rate; hyperbolic discounting; the sign effect; the probit model